Paper 18: Effect of Bone Marrow Aspirate Concentrate on Osteochondral Allograft Transplantation Incorporation: A Prospective, Randomized, Single Blind Investigation. Issue 7 (30th July 2022) - Yanke, Adam; Dandu, Navya; Bodendorfer, Blake; Darwish, Reem; Zavras, Athan; Forsythe, Brian; Cole, Brian; Trasolini, Nicholas
Objectives: Osteochondral allograft transplantation for cartilage defects of the knee has demonstrated excellent long-term clinical outcomes and survival, which largely depends on successful graft osseointegration. Biologics have been suggested as a viable adjunct to enhance successful healing in several musculoskeletal applications. In the context of OCA, early results have suggested that BMAC may improve cellular repopulation and viability within the osseus portion of an implanted graft. However, few clinical studies to date have investigated the impact of BMAC on patient outcomes following OCA. The purpose of this study was to investigate the effect of bone marrow aspirate concentrate (BMAC) on osseointegration and patient-reported outcome metrics (PROMs) after osteochondral allograft transplantation in a prospective, randomized controlled single-blinded trial. Methods: Patients undergoing osteochondral allograft transplantation of the knee were consented and enrolled. Prior to surgery, patients were randomized into either the BMAC or sham incision groups. In the BMAC group, the osteochondral allograft plug was soaked in BMAC for a minimum of 2 minutes prior to implantation. All patients underwent postoperative computed tomography (CT) scanning at 6 months postoperatively and completed PROMs preoperatively, 6 months, and 1 year postoperatively. Two board-eligible orthopaedic surgeons blinded to treatment allocation independently assessed and graded each CT according to the ACTOCA system proposed by Gelber et al . Results: Thirty-six patients enrolled between April 2018 to December 2020 (17 female, 19 male) were included for analysis. There were no significant differences between the BMAC and non-BMAC groups in graft signal density (Grader 1: p=0.283, Grader 2: p=0.467), osseous integration (both graders: p=0.489), surface percentage with discernible cleft (Grader 1: 0.287, Grader 2: 0.469), or intra-articular fragments (Grader 1: p=0.617, Grader 2: p=0.810) (Table 1 ). A significantly greater number of patients receiving BMAC demonstrating cystic changes <3 mm (Grader 1: p=0.015, Grader 2: p=0.05) (Figure 1 ). At 1 year, BMAC patients reported significantly better WOMAC Pain (87.82±14.26 vs 75.80±15.56, p=0.043) and trended towards improved PROMIS Pain (54.14±8.31 vs 61.79±5.24, p=0.09). Conclusions: Patients receiving BMAC soaked OCA grafts demonstrated no difference from controls with respect to graft signal intensity, osseous integration, intra-articular fragments, or discernible graft-host clefts at 6-months postoperatively. BMAC patients had a significantly greater occurrence of small (<3 mm) cystic changes. At 1 year, BMAC patients reported significantly less pain than controls on WOMAC Pain, with similar trends on PROMIS Pain Interference. Table 1. Postoperative Imaging Characteristics (ACTOCA) by Grader. Figure 1. Distribution of cystic changes between BMAC and control groups.